2021
DOI: 10.24198/jaab.v4i1.31551
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors Enterprise Resource Planning (ERP) Implementation in Higher Education

Abstract: One of the technologies that can optimize the data management system in Higher Education is the Enterprise Resource Planning (ERP) information system. However, in its implementation, failures often occur. This research was conducted to formulate the key factors for the successful implementation of ERP systems in universities. The research method used is descriptive qualitative through case studies on 4 campuses in West Java. The 20 key factors taken are the result of iterations of 32 works of literature in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…On the other hand, it is also found that System Quality and Consultant Support are also important factors when it comes to ERP implementation. This is consistent with the studies of Rizkiana et al, [17].…”
Section: Multiple Regression Analysissupporting
confidence: 94%
See 2 more Smart Citations
“…On the other hand, it is also found that System Quality and Consultant Support are also important factors when it comes to ERP implementation. This is consistent with the studies of Rizkiana et al, [17].…”
Section: Multiple Regression Analysissupporting
confidence: 94%
“…Wang and Chen [23] argued about the importance of Consultant Support for the successful ERP implementation. Rizkiana, et al, [17] also supported the argument that consultant support is a critical success factor of ERP implementation. Moreover, study findings [10] assert the presence of significant causal relationship between the consultant support and the ERP system performance.…”
Section: Consultant Support and The Erp Successmentioning
confidence: 89%
See 1 more Smart Citation
“…The implementation of ERP technology in universities enables efficient and cost-effective office administration, personnel management, and procurement, whilst reducing paper usage in administrative correspondence (Maulana, 2018). The primary reason for universities to adopt ERP is to improve their student services and to maintain a competitive edge through improved operational efficiency (Rizkiana et al, 2021). Due to modern developments in technology and globalisation, the nature of higher education (HE) is evolving continuously, with many institutions of various sizes and types struggling to remain competitive by strengthening their technological skills alone.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AISs are usually implemented before any other business application since they ensure mandatory regulations compliance (i.e., bookkeeping and financial statements disclosure) [13]. AISs (even when cloud-based) currently in use by all the companies are designed as centralised systems [14][15][16] to ensure security principles as confidentiality [17,18], controllability (direct access and liberate chain of command) [19] and costeffectiveness [20,21]. Moreover, all other business applications are built in the ERPs around the AISs to gather and provide (input or output) data for further analyses, consistent with the accounting results [13,22,23].…”
Section: Introductionmentioning
confidence: 99%